THE EFFECT OF HUMAN RESOURCES COMPETENCE ON THE GOVERNMENT IMPLEMENTATION OF INTERNAL CONTROL SYSTEM, ACCRUAL BASED ACCOUNTING STANDARDS AND THE QUALITY OF LOCAL GOVERNMENT’S FINANCIAL REPORT - Razak, Jaeluddin; Abdullah, Muntu; Dali, Nasrullah (Pascasarjana Universitas Halu Oleo, 2017)
The study aimed to find out the effect of human resources competence towards the quality of Local Government financial report in Konawe Regency through implementing internal control systems and accrual based accounting standards as the intervening variables. Population of the study was the entire SKPD (Government Agency) under the Government of Konawe Regency and the respondents of the study were selected through purposive sampling technique. The respondent in this study was the officials of Pejabat Penatausahaan Keuangan Satuan Kerja Perangkat Daerah (PPK-SKPD) which consisted of 52 numbers. Data in this study was analyzed descriptively and inferentially utilizing SPSS Software 20 through Path Analysis.The reseach result show that, the competence of human resources had a positively significant effect into the implementation of government internal control systems. The variable of human resources competence had a positively significant effect into the implementation of accrual based accounting standards. The variable of human resources competence positively and significant affected the quality of financial report of the local government. The variable of government internal control systems had a positively significant effect into the quality of financial report of the local government. The variable of accrual based accounting standardshad a positively significant effect towards the quality of financial report of the local government. The variable of human resources competence had a positively significant effect on the quality of financial report of the local government through the implementation of government internal control systems, and the variable of human resources competence had a positively significant effect towards the quality of financial report through the implementation of accrual based accounting standards. Keywords: Human Resources Competence, Government Internal Control Systems, Accrual Based Aaccounting Standards, The Quality of Government Financial Reports.